2019
DOI: 10.1021/acsaem.8b02141
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fluoride Doping on Lithium Diffusivity in Layered Molybdenum Oxide

Abstract: The effects of cation doping on cathode performance has been extensively studied; however, the field of anion doping has historically received much less attention. Fluoride doping can greatly increase the initial diffusivity of the layered MoO3 system. The first discharge cycle of the layered α-MoO3 and MoO2.8F0.2 phases were investigated and compared using the galvanostatic intermittent titration technique (GITT) in a lithium ion cell. The analysis revealed that a slight reduction of the oxide by fluoride dop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…As was observed from cyclic voltammetry, the intrinsic instability of MoO 3 led to a poor capacity retention of ∼44% (67.2 mA h g –1 ) after 1000 cycles. For long-term cycling, further work is necessary to either stabilize the MoO 3 crystal structure, which has been the topic of recent investigation, ,, or determine an aqueous electrodeposition route for an oxide material that does not undergo such significant structural change.…”
Section: Resultsmentioning
confidence: 99%
“…As was observed from cyclic voltammetry, the intrinsic instability of MoO 3 led to a poor capacity retention of ∼44% (67.2 mA h g –1 ) after 1000 cycles. For long-term cycling, further work is necessary to either stabilize the MoO 3 crystal structure, which has been the topic of recent investigation, ,, or determine an aqueous electrodeposition route for an oxide material that does not undergo such significant structural change.…”
Section: Resultsmentioning
confidence: 99%
“…These facts seem to show NaMoO 3 F was obtained in topotactic manner, in which MoO 3 layers were cut by insertion of NaF with substitution of oxygen to fluorine. Such topotactic reaction may be possible, because it was reported that one of molybdenum oxyfluorides, MoO 2.8 F 0.2 , was obtained by topotactic reaction in the hydrothermal reaction …”
Section: Resultsmentioning
confidence: 99%
“…The difference in the rod length between the pristine MoO 3 and MoO 3 _NaF_CH 3 CN_200 may be derived from the fracturing by the dissolution or the mechanical force during the reaction. Therefore, two mechanisms are possible in the case of CH 3 CN: (i) the complete dissolution–reprecipitation mechanism or (ii) simultaneous occurrence of the dissolution and the topotactic reaction and the subsequent growth on the topotactically formed NaMoO 3 F. Although we cannot understand which manner is real yet, the topotactic fluorination under solvothermal condition offers a new design concept for synthesizing mixed anion materials . However, the SEM image of the sample after the reaction in EtOH for 1 h (Figure S7E) shows the mixture of the rod shape and polyhedral morphology, while that of the samples after the reaction in EtOH for 5 h (Figure S7F) shows only the polyhedral morphology.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure a shows the α-MoO 3 electrode delivered 236 and 165 mA h g –1 at a current density of 20 mA g –1 for the first discharge and charge capacity, respectively, with 83 mA h g –1 irreversible capacity in the first cycle, which will be discussed later. This irreversible capacity is no longer observed after the first cycle . The α-MoO 3 electrode reversibly delivered a specific capacity of 165 mA h g –1 (discharge capacity basis), corresponding to 0.44 mol of Ca 2+ /MoO 3 .…”
mentioning
confidence: 96%